2020
DOI: 10.1002/bse.2511
|View full text |Cite
|
Sign up to set email alerts
|

Effect of local government decision‐making competition on carbon emissions: Evidence from China's three urban agglomerations

Abstract: Analyzing the effect of local government decision‐making competition on regional carbon emissions is important for reducing carbon emissions in rapidly urbanizing areas. Taking the energy rebound effect into account, this study analyzes the effect on carbon emissions of competition between local governments in decision making. Focusing on China's three urban agglomerations, this study further discusses how to avoid this influence. The results show that local government decision‐making competition is one of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…As a result, new officials often appear to negate the industrial policies formulated by their predecessors [47], resulting in the government's implementation of industrial policies that often deviate from the policy objectives. Large amounts of resources flow in and out frequently within different industries [48], constraining the optimization and upgrading of regional industrial structures. It has been shown that industrial restructuring and upgrading is an important factor in developing a low-carbon economy [49][50][51], while Gu et al [52] further showed that industrial restructuring and upgrading is an effective driver of CO 2 emission reduction, as well as a fundamental driver of the low-carbon development of the industrial system.…”
Section: Indirect Impact Of Economic Growth Goals On Carbon Emissionsmentioning
confidence: 99%
“…As a result, new officials often appear to negate the industrial policies formulated by their predecessors [47], resulting in the government's implementation of industrial policies that often deviate from the policy objectives. Large amounts of resources flow in and out frequently within different industries [48], constraining the optimization and upgrading of regional industrial structures. It has been shown that industrial restructuring and upgrading is an important factor in developing a low-carbon economy [49][50][51], while Gu et al [52] further showed that industrial restructuring and upgrading is an effective driver of CO 2 emission reduction, as well as a fundamental driver of the low-carbon development of the industrial system.…”
Section: Indirect Impact Of Economic Growth Goals On Carbon Emissionsmentioning
confidence: 99%
“…In addition, in the process of evaluation, local governments may deviate from the main purpose and blindly invest resources, sometimes causing high costs and social tension (Zhang & Li, 2011). On the issue of competition promoting innovation, local governments may attract more FDI by lowering the standards of environmental regulation, which will inhibit regional innovation performance and mutual imitation (Deng et al., 2019), and competition to the bottom may also distort the factor market and investment preference in the decision‐making competition of local governments (Li & Xu, 2020). Therefore, the comprehensive effect of the PCM in local governance is still deserved to carry out further research.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the High-High clusters were mainly concentrated in the Shandong Peninsula, such as Dongying, Jinan, linyi, Zibo, and Binzhou. However, the High-High clusters spread to Hohhot and Baotou in 2019, one possible reason is that local officials tend to glorify their political performance by focusing on economic growth rather than pollution reduction, and this leads to the “race to the bottom” in the High-High clusters [ 33 ]. While the Low-Low agglomerations were mainly distributed in the upstream and midstream cities, including Qingyang, Yan’an, Yulin, Linfen, Pingliang, Tianshui, Tongchuan, Longnan, Zhongwei, Baiyin, and Dingxi, highlighting the spatial heterogeneity of carbon emissions in the YREB.…”
Section: Empirical Analysismentioning
confidence: 99%